Normal cerebral cortical thickness in first-degree relatives of temporal lobe epilepsy patients. (22nd January 2019) - Alhusaini, Saud; Kowalczyk, Magdalena A.; Yasuda, Clarissa L.; Semmelroch, Mira K.; Katsurayama, Marilise; Zabin, Matheus; Zanão, Tamires; Nogueira, Mateus H.; Alvim, Marina K.M.; Ferraz, Victória R.; Tsai, Meng-Han; Fitzsimons, Mary; et al.
Abstract : Objective: To examine cerebral cortex thickness in asymptomatic first-degree relatives of patients with mesial temporal lobe epilepsy (MTLE). Methods: We investigated 127 asymptomatic first-degree relatives of patients with MTLE due to hippocampal sclerosis (HS) (mean age ± SD = 39.4 ± 13 years) and 203 healthy control individuals (mean age ± SD = 36.0 ± 11 years). Participants underwent a comprehensive clinical evaluation and structural brain MRI at 3 study sites. Images were processed simultaneously at each site using a surface-based morphometry method to quantify global brain measures, hippocampal volumes, and cerebral cortical thickness. Differences in brain measures between relatives of patients and controls were examined using generalized models, while controlling for relevant covariates, including age and sex. Results: None of the asymptomatic first-degree relatives of MTLE + HS patients showed evidence of HS on qualitative image assessments. Compared to the healthy controls, the asymptomatic relatives of patients displayed no significant differences in intracranial volume, average hemispheric surface area, or hippocampal volume. Similarly, no significant cerebral cortical thinning was identified in the relatives of patients. This was consistent across the 3 cohorts. Conclusion: Lack of cortical thickness changes in the asymptomatic relatives of patients indicates that the previously characterized MTLE + HS-related cortical thinning is not heritable, and is likely driven by disease-related factors. This finding therefore argues for early and aggressive intervention in patients with medically intractable epilepsy.